Experimental Performance Analysis of A Solar Hybrid Recirculating Mixed-Flow Dryer With Different Drying Temperatures For Drying Paddy - Yahya, Muhammad; Wardianto, Dedi; Pratiwi, P (Universitas Negeri Padang, 2025)
This study is focussed on the performance of a solar hybrid recirculating mixed-flow dryer (SHRMFD) for drying paddy with different drying air temperatures. The drying experiments were carried out at average air temperatures of 50 °C, 60 °C and 70 °C. The SHRMFD reduced the mass of paddy from 420 kg (16.90% wb) to 406.07 kg (14.17% wb) in 360 min; from 420 kg (16.80 % wb) to 407.63 kg (14.17%) in 165.4 min; from 420 kg (16.75 % wb) to 407.35 kg (14.17% wb) in 143.3 min for average air temperatures of 50°C, 60°C and 70°C, respectively. The highest drying rate (3,324 kg/hour) was achieved at an average air temperature of 70°C. The specific moisture evaporation rate (0.171kg/kWh) and thermal efficiency of SHRMFD (25.04%) were achieved highest at an average air temperature of 50°C. The lowest specific energy consumption (11.804 kWh/kg) was achieved at an average air temperature of 50°C. The energy contributed by the biomass furnace and the solar collector for SHRMFD were 13.28 and 14.74%; 8.08 and 17.50%; and 6.10 and 20.35 for average air temperatures of 50°C, 60°C and 70°C, respectively. The SHRMFD performance is better at an average air temperature of 50°C because it has higher thermal efficiency and lower energy consumption.